The Impact of Gamification on User Engagement and Motivation in Fitness Apps - Balabayova, Leyla; Sudzina, František; Ziaei Nafchi, Majid; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis examines how gamification supports motivation and long-term engagement in mobile fitness apps. Building on Self Determination Theory, Flow Theory, Goal Setting Theory, and user experience principles, it analyzes OnlyFits, a fitness platform that combines structured workout plans with tracking and social features. Survey data from active users were used to test a motivational model linking gamification, psychological mechanisms, and engagement. Results indicate that gamification fosters engagement mainly through competence and relatedness satisfaction, flow experiences created by balanced challenge and skill, and clear goal structures with frequent feedback. Autonomy played a limited role in this structured environment. Usability acted as a basic requirement but did not predict motivation once gamification was considered. Flow and goal setting functioned as central mediators, and competence moderated the strength of gamification effects. The study offers an integrated framework showing how need fulfilment, experiential absorption, and goal regulation work together to support intrinsic motivation in fitness apps. It also provides design guidance that prioritizes adaptive feedback, meaningful social interaction, and progressive challenge to promote sustained behaviour change.
Vedoucí práce: František Sudzina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: data and business [obor dipl. práce]; diplomové práce; master's theses